A Review on Biomolecular Mechanisms of Parkinson’s Disease - Mahalakshmi, P. Sree (International Journal of Pharmaceutical & Biological Archive, 2021)
Degeneration of catecholaminergic (dopamine) neurons in the Substantia Nigra pars compacta of the basal ganglia results in Parkinson’s disease (PD). The drug of choice is L-dopa, anticholinergics, amantadine, monoamine oxidase-B inhibitors, dopamine agonists, and catechol O-methyl transferase inhibitors are used. Therapeutic strategies are currently managing the symptoms of PD, but not curing the disease. This review draws insights on the molecular mechanisms driving the loss of brain cells in PD.